Glycated haemoglobin and the risk of postoperative complications in people without diabetes: a prospective population‐based study in UK Biobank. (3rd March 2022) - Lam, S.; Kumar, B.; Loke, Y. K.; Orme, S. E.; Dhatariya, K.
Abstract : Summary The aim of our study was to clarify the association between glycated haemoglobin (HbA1c ) and postoperative outcomes in people without an existing diagnosis of diabetes. Half a million adults were recruited into the UK Biobank prospective cohort study between March 2006 and October 2010. We divided participants into three groups: no diagnosis of diabetes and HbA1c  < 42 mmol.mol −1 ; no diagnosis of diabetes and elevated HbA1c (≥ 42 mmol.mol −1 with no upper limit); and prevalent diabetes (regardless of HbA1c concentration) at recruitment. We followed up participants by linkage with routinely collected hospital data to determine any surgical procedures undertaken after recruitment and the associated postoperative outcomes. Our main outcome measure was a composite primary outcome of 30‐day major postoperative complications and 90‐day all‐cause mortality. We used logistic regression to estimate the odds of the primary outcome by group. We limited analyses to those who underwent surgery within one year of recruitment (n = 26, 653). In a combined effects logistic regression model, participants not known to have diabetes with HbA1c  ≥ 42 mmol.mol −1 had increased odds of the primary outcome (OR [95% CI] 1.43 [1.02–2.02]; p = 0.04), when compared with those without diabetes and HbA1c  < 42 mmol.mol −1 . This effect was attenuated and no longer statistically significant in a direct effects model with adjustment for hyperglycaemia‐related comorbidity (OR [95% CI] 1.37 [0.97–1.93]; p = 0.07). Elevated pre‐operative HbA1c in people without diabetes may be associated with an increased risk of complications, but the association is likely confounded by end‐organ comorbidity. In contrast to previous evidence, our findings suggest that to prevent adverse postoperative outcomes, optimisation of pre‐existing morbidity should take precedence over reducing HbA1c in people without diabetes.